FIGURES 12–19 in The plagiatus species group of the genus Geodromicus Redtenbacher, 1857 (Insecta Coleoptera: Staphylinidae: Omaliinae), and additional data on some species from Japan - Shavrin, Alexey V. (Zenodo, 2022)
FIGURES 12–19. Aedeagus (parameral view) of Geodromicus plagiatus: 12–France, Bious Artiguer, 13–France, Gavarnie, 14–Czech Republic, Nový Svĕt, 15–Sweden, Abisko, 16–Sweden, Vistbäcken, 17–Russia, Karachay-Cherkessia, Elbrus, 18– 'Kaukasus' (paratype of G. schoenmanni), 19–Russia, Murmansk Area, Yläluostari. Scale bars: 0.1 mm. Published as part of Shavrin, Alexey V., 2022, The plagiatus species group of the genus Geodromicus Redtenbacher, 1857 (Insecta Coleoptera: Staphylinidae: Omaliinae), and additional data on some species from Japan, pp. 401-429 in Zootaxa 5188 (5) on page 412, DOI:10.11646/zootaxa.5188.5.1, http://zenodo.org/record/7099200